Assessing probiotic viability in mixed species yogurt using a novel propidium monoazide (PMAxx)-quantitative PCR method - Marole, Tlaleo A.; Sibanda, Thulani; Buys, Elna M. (Frontiers in Microbiology, 2024)
Viability is a prerequisite for any therapeutic benefits associated with the ingestion of probiotic bacteria. Current culture-based techniques are inadequate for the enumeration of probiotics in mixedspecies food products. This study utilized a quantitative PCR (qPCR) method coupled with PMAxx, and novel species-specific tuf gene primers to selectively enumerate Lacticaseibacillus rhamnosus, Bifidobacterium spp., and yoghurt starter cultures in mixed-species probiotic yoghurt. The method was optimized for PMAxx concentration and specificity and evaluated for efficiency and applicability.PMAxx-qPCR showed high specificity to the target organisms in mixed-species yoghurt, quantifying only viable cells. The linear dynamic ranges were established over five to seven orders of magnitude.The assay was reliable with an efficiency of 91-99%, R 2 values > 0.99, and a good correlation to the plate count method (r = 0.882). The results of this study demonstrate the high selectivity, improved lead time, and reliability of PMAxx-qPCR over the culture-dependent method, making it a valuable tool for inline viability verification during processing and improving probiotic quality assurance for processors and consumers.